Urban Agriculture Development in Medan City Towards Food Sovereignty - Nasution, Faiz Albar; Indainanto, Yofiendi Indah; Anshari, Andry; Saraan, Muhammad Imanuddin Kandias; Pardede, Piki Darma Kristian; Imam Fahreza (Journal of Peasants' Rights, 2022)
Medan has enormous potential for expanding urban agriculture for achieving food security. The primary issues in achieving the urban agricultural movement are consistency and cooperation. The goal of this essay is to show how the city of Medan's agricultural policies can boost food independence while also improving the economy. This study employs a qualitative descriptive research method with a literature review approach. Data analysis techniques include data reduction, data visualization, and making conclusions. The findings indicate that urban agriculture plays an important role in community empowerment through the food self-sufficiency movement. The advantages can lead to new work prospects. It is critical to increasing cooperation between local governments and the community through policy protection and aid for the development of plant management expertise and harvest marketing distribution.